European initiatives - chances for universities - Hijden, Peter van der (Univerzita Pardubice, 2014)
Universities play a central role in the development of their country. They produce and process knowledge and transmit this knowledge to the next generation, to the economy and to society at large. Universities need to take action in order to become even more successful players at local, regional, national, European and international level. Actions include modernisation in education, research and innovation. Special attention should be given to human resources management and doctoral training. European initiatives can act as a catalyst.
Keywords: European Higher Education Area; European Research Area; modernising universities; EU programmes